Allogeneic hematopoietic cell transplantation for older patients with Philadelphia-positive acute lymphoblastic leukemia: a study by the Acute Leukemia Working Party of the EBMT - Giebel, Sebastian; Labopin, Myriam; Swoboda, Ryszard; Blaise, Didier; Yakoub-Agha, Ibrahim; Nguyen, Stephanie; Wagner-Drouet, Eva Maria; Castilla-Llorente, Cristina; Kottaridis, Panagiotis; Schroeder, Thomas; Fanin, Renato; Passweg, Jakob; et al. (Bone marrow transplantation, 2025)
The role of allogeneic hematopoietic cell transplantation (allo-HCT) in older patients with Philadelphia-positive acute lymphoblastic leukemia (Ph+ ALL) is not well established. In this retrospective analysis we evaluated outcomes of 566 patients with median age of 60 (range 55-76) years treated in first complete remission with allo-HCT from either a matched sibling (n = 138), unrelated (n = 343) or haploidentical (n = 85) donor between the years 2016 and 2022. The probability of overall survival (OS) and leukemia-free survival (LFS) at 2 years was 71% and 59.5%, respectively. The incidence of relapse, and non-relapse mortality (NRM) was 18% and 22.5%, respectively. The rate of graft-versus-host disease (GVHD)-free, relapse-free survival was 50%. In a multivariate model, the use of total body irradiation (TBI) was the only factor affecting outcomes, being associated with reduced risk of NRM (hazard ratio, [HR] = 0.46, p = 0.004), improved LFS (HR = 0.53, p < 0.001) and OS (HR = 0.47, p < 0.001) as well as increased risk of chronic GVHD (HR = 1.68, p = 0.009) and extensive chronic GVHD (HR = 1.84, p = 0.04). We conclude that in the last few years, outcomes of allo-HCT for patients with Ph+ ALL aged ≥55 years are encouraging. TBI-based reduced intensity conditioning appears preferable in this patient population. Our data can serve as a reference for future prospective trials.